Pengaruh Implementasi Media Videoscribe Berbasis E-Learning Terhadap Hasil Belajar Tematik Pada Siswa Kelas V Madrasah Ibtidaiyah - Mei Akbar Velayati; Ichsan Djalal (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by the existence of problems related to thematic learning outcomes of students in the theme of 7 events in life. It was found in the initial observations, that student learning outcomes were still below the KKM ≤79 (86%) of 37 students. In this regard, the researcher aims to describe: 1) the implementation of e-learning-based videoscribe media, 2) the learning outcomes before and after applying the videoscribe media, and 3) the effect of the e-learning-based videoscribe media implementation on thematic learning outcomes in fifth grade students. This research uses quantitative methods. This type of research is a quasi-experimental design with the non-equivalent control group design research design. The research location is at Madrasah Ibtidaiyah Negeri 3 Pontianak. This research is carried out in class V in the even semester of the 2021/2022 academic year. The data was collected by means of observation, measurement techniques, and document studies. The data collection tools are observation sheets, learning outcomes tests, and electronic devices. While the data analysis is using descriptive analysis, and bivariate analysis. This research concludes: 1) The implementation of e-learning-based videoscribe media on thematic learning outcomes has been in accordance with the implementation steps. 2) Learning outcomes before applying the videoscribe media obtained a percentage of (9%) of 4 students who met the KKM ≥79 with an average learning outcome of 62,40. Furthermore, the learning outcomes after applying the videoscribe media obtained a percentage of (95%) of 41 students who met the KKM ≥79 with an average learning outcome of 86,21. 3) Based on data analysis, the value of Approx is obtained. Sig = 0,000 with (α)=0,05. If the value of Approx. Sig < = (0,05), then H0 is rejected. So it can be said that there is a significant effect between the implementation of e-learning-based videoscribe media on thematic learning outcomes in class V students of MIN 3 Pontianak in the 2021/2022 academic year. And the large influence of the implementation of e-learning-based videoscribe media on thematic learning outcomes is obtained by 43% in the sufficient category, in the sense that the learning process is very effective and student learning outcomes are above average.